Analisis Keefektifan Pembelajaran Kimia Secara Online di Masa Pandemi Covid-19 Di SMAN 1 Gerung - Erfanny, Anjelina; Haris, Mukhtar; Hadisaputra, Saprizal; Junaidi, Eka (FKIP University of Mataram, 2024)
This study aims to determine the effectiveness, constraints, and efforts during chemistry learning takes place online during the Covid-19 Pandemic at SMAN 1 Gerung, West Lombok Regency. The method used in this research is descriptive qualitative. The data collected is in the form of a questionnaire filled by 72 samples. The research sample was taken by simple random sampling that has been calculated with the slovin formula. Results of data analysis the research questionnaire on all indicators produces an average value successively with less effective aspects as follows: indicators process communication 3,40 indicators management of the implementation of learning 3,20, indicators student response 3,32, indicators learning activity 3,10, and indicators outcome student learning 3,20. Online chemistry learning in the future the Covid-19 pandemic at SMAN 1 Gerung, West Lombok Regency, is still lacking effective with an average value of 3.24. Constraints during learning takes place online, namely an unstable internet connection, limited quota internet, and there are students who do not have cellphones. Efforts made to overcome obstacles, namely the teacher visits the student's house to give learning and limited face to face learning.